External fixation of airway stents for upper tracheal stenosis and tracheoesophageal fistula. (20th April 2021) - Niwa, Hideyuki; Oki, Masahide; Saka, Hideo; Torii, Atsushi; Yamada, Arisa; Shigematsu, Fumie; Ishida, Akane; Kogure, Yoshihito
Abstract:  : OBJECTIVES: Stent migration is a common complication of airway stent placement for upper tracheal stenosis and tracheoesophageal fistula. Although several researchers have reported that external fixation is effective in preventing stent migration, the usefulness and safety of external fixation have not been proved because their cohorts were small. We therefore investigated the efficacy and safety of external fixation during upper tracheal stenting. METHODS: Records of patients who underwent airway stent placement from May 2007 to August 2018 in a single centre were retrospectively reviewed. We included only patients whose stent had been placed in the upper trachea with external fixation to the tracheal wall. The primary endpoint of this study was the rate of stent migration. RESULTS: Altogether, 51 procedures were performed in 45 patients (32 males, 13 females; median age 60 years, range 14–91 years). The median follow-up period was 9 months (range 0.3–90 months). Among the procedures, 15 were performed for benign disease and 36 for malignancy. Stents were composed of either silicone ( n  = 42) or metal ( n  = 9). Stent migration occurred in 3 (6%) patients. The stents with migration were all composed of silicone. Other sequelae were granulation tissue formation in 10 (20%) patients, sputum obstruction in 6 (12%), cellulitis in 3 (6%) and pneumonia in 1 (2%). CONCLUSIONS: External fixation was an effective method for preventing migration of airway stents placed for upper tracheal stenosis and tracheoesophageal fistula. The complications were acceptable in terms of safety.